Linkage between Utah All Payers Claims Database and Central Cancer Registry. (24th January 2019) - Garvin, Jennifer Hornung; Herget, Kimberly A.; Hashibe, Mia; Kirchhoff, Anne C.; Hawley, Charles W.; Bolton, Dan; Sweeney, Carol
Abstract : Objective: To evaluate the linkage of claims from the Utah All Payers Claims Database (APCD) and Utah Cancer Registry (UCR). Data Sources: Secondary data from 2013 and 2014 Utah APCD and 2013 UCR cases. Study Design: This is a descriptive analysis of the quality of linkage between APCD claims data and cancer registry cases. Data Collection/Extraction Methods: We used the LinkPlus software to link Utah APCD and UCR data. Principal Findings: We were able to link 82.4 percent (9441/11 453) of the UCR reportable cancer cases with APCD claims. Of those linked, 66 percent were perfect matches. Conclusions: The quality of identifiers is high, evidence that claims data can potentially supplement cancer registry data for use in research.